Identification of the cause of severe skin infection by Fournier transform infrared spectroscopy: A case of Fournier's gangrene caused by fish bone. Issue 6 (June 2014) - Shimizu, Takae; Harada, Kazutoshi; Akazawa, Satoshi; Yamaguchi, Miyuki; Inozume, Takashi; Kawamura, Tatsuyoshi; Shibagaki, Naotaka; Momosawa, Akira; Shimada, Shinji
Abstract Fournier's gangrene (FG) is an infrequent but highly lethal infection. Here we report a 74‐year‐old man who presented with genital swelling and severe malaise. Based on the physical and imaging examination results, the diagnosis of FG was confirmed. Intraoperative findings showed dirty necrosis of soft tissue, and a splinter‐shaped foreign body was found in the perirectal region. The foreign body was thought to be the cause of the condition, and it was analyzed using Fourier transform infrared spectroscopy. We found that the foreign body was a mixture of calcium phosphate and protein, suggesting that the splinter was a bone. Moreover, during the medical interview, the patient mentioned about intake of fish around the time of onset of symptoms. Therefore, to confirm the results of the analysis, DNA was extracted from the foreign body, and genomic PCR with subsequent sequence analysis was performed. The DNA sequence was identical to that of Oncorhynchus kisutch, a salmon that is a very popular food in Japan. On the basis of these findings, we concluded that FG in this case was caused by the penetration into the rectum of an accidentally ingested fish bone. Although some cases of intra‐abdominal abscess due to accidental ingestion of fish bone have been reported, FG caused by fish bone is extremely rare.